Modelos computacionais ultrassônicos com ênfase na emulsão O/A - Leão, Rodrigo Xavier de Almeida (2015)
This work proposes a study simulating the use of ultrasonic probes and ultrasound bath applied in emulsions produced by the oil industry, specifically, the emulsions of oil-in-water (o/w) found in produced water. The first part of the study consisted in an analytical solution of the Bessel equation in order to study the formation of the radial pattern of standing waves in a cylindrical container containing the o/w emulsion at low (24 kHz) and high (1.841 MHz) frequency, from an ultrasound transdutor located at the center of the container. The second part of the study consisted in the construction and application of a computer model capable of representing the displacement of the ultrasonic waves within an ultrasonic bath containing a container filled with an o/w emulsion, synthesized from petroleum with 13.1 ° API in the presence of materials. The analytical solution of the Bessel equation estimated frequency to 24 kHz ultrasonic probes, the first three stationary vibration modes occur respectively in radius containers 34.45; 54.01 and 73.60 cm. When the simulation was applied to ultrasonic probes frequency 1.841 MHz estimated that three stationary vibration modes occur respectively in containers radius 0.45; 0.70 and 0.96 cm. The results of the computer model simulating the displacement of the ultrasonic waves within an ultrasonic bath proved according to experimental results, permitting identification of the increased density of the acoustic field that occurs due to the presence of material within the emulsion as the main responsible for the high efficiency in the removal of this oil fraction in the emulsions under the action of ultrasonic fields of low frequency. Was estimated as a material is capable of increasing the density of the sound field compared to a container without the presence of materials, being: 1.47 to Teflon, 2.05 to PVC, 2.07 to polypropylene, 2.17 for aluminum, 2.87 to copper, 3.00 to nickel, 3.01 to brass, 3.09 to steel and 3.72 to lead. The area occupied by the material within the container proved responsible for the amount of energy retained therein. The influence of the variation of the area of the materials present in the emulsion was also assessed from the results of the developed model.